Energy performance investigation of nanofluid‐based concentrated photovoltaic / thermal‐thermoelectric generator hybrid system. (25th January 2021) - Lekbir, Abdelhak; Hassani, Samir; Mekhilef, Saad; Saidur, R.; Ab Ghani, Mohd Ruddin; Gan, Chin Kim
Summary: Nanofluid can be used in a CPV/T solar collector to boost electrical and thermal performances as this technology has drawn great attention from researchers over the last decades. In a CPV/T system, the amount of collected heat could be significantly higher than the amount of electrical power. Combining thermoelectric generator (TEG) and nanofluid‐based CPV/T system may result in better electrical performance than CPV/T system alone. In the present work, a nanofluid‐based CPV/T‐TEG hybrid system with a cooling channel was designed and tested, and the obtained performance was compared with conventional cooling methods [ie, natural cooling (CPV/TEG) and water cooling (WCPV/T‐TEG) methods]. At the optimum value of solar concentration, C = 14.6, the electrical performance of the nanofluid‐based concentrated photovoltaic/thermal‐thermoelectric generator (NCPV/T‐TEG) configuration was found to be ~89% higher than the standard PV modules. For the same concentration, the electrical performance of the above configuration was found to be ~13.9% and ~8.4% higher than CPV/TEG and WCPV/T‐TEG configurations, respectively. In addition, the overall thermal energy of the NCPV/T‐TEG was found to be higher by 4.98% compared to WCPV/T‐TEG hybrid system. The NCPV/T‐TEG configuration was found to produce 92.47%, 41.06%, and 8.8% higher daily exergy compared to standard PV cell, CPV/TEG, and WCPV/T‐TEG, respectively. Overall, the proposed design of the NCPV/T‐TEG hybrid system has the potential for further development in high‐concentration solar systems. Abstract : A novel nanofluid‐based concentrated photovoltaic/thermal‐thermoelectric generator hybrid system was developed and tested to improve the solar energy conversion rate. The thermoelectric generator (TEG) acted as a second power generator to boost the overall electrical power of the hybrid system. The electrical and thermal performances of the hybrid system have been investigated experimentally under different cooling modes, that is, natural cooling, water‐based cooling, and CNT nanofluid‐based cooling. Obtained findings confirmed the advantages of combining photovoltaic cells and TEG generator using CNT nanofluid as a cooling fluid.